Challenges faced by mothers with human immunodeficiency virus positive children in Pietersburg Hospital, Limpopo Province South Africa - Segoale, Nare Okney (My University, 2020)
The purpose of the study was to identify and explore the challenges faced by mothers with HIV positive children and who were admitted to Pietersburg Hospital, Limpopo Province, South Africa, during the period of study. A qualitative research methodology was used in the study based on exploratory and descriptive designs. The population for the study included all mothers of children who are HIV positive and had been admitted to the Paediatric Ward of Pietersburg Hospital, Limpopo Province, during the period of study. Non-probability purposive sampling was used to draw a sample of twelve (12) HIV positive participants from the research population. Data was collected from twelve participants through the use of semi-structured in-depth interviews, guided by an interview schedule. Fields notes were captured for non-verbal communication and a voice recorder was used to capture all the audio record of the interview sessions. Ethical clearance for the study was obtained from Turfloop Research Ethics Committee (TREC); and permission to collect data at the Pietersburg Hospital was obtained from the Limpopo Department of Health as well as the hospital’s Chief Executive Officer and from the Operational Manager of the Paediatric Ward. The findings from the study indicated that mothers of HIV positive children experienced numerous psychosocial and economic challenges on a daily basis. These challenges include accepting their own and their children’s HIV positive status; and also disclosing the status to their children. They also had to deal with opportunistic infections that the HIV positive children are more susceptible to, as well as challenges of ensuring that their children did not default on the medication schedules. Poverty and the lack of finances to pay for the various special needs of HIV positive children were also other key challenges experienced by the mothers. In light of these findings the study recommends the need for HIV/AIDS education, support from families and significant others as well as from the government. The study also recommends that well-coordinated and integrated inter-departmental intervention programmes are required to help mothers cope with their challenges.
Thesis(M.A.(Nursing)) -- University of Limpopo, 2020
Keywords: Challenges; HIV/AIDS; Mothers; Children; Immunodeficiency; Mothers; AIDS (Disease); HIV (Viruses); HIV-positive children